Routine molecular point-of-care testing for SARS-CoV-2 reduces hospital-acquired COVID-19. Issue 4 (April 2022) - Livingstone, Robert; Lin, Hlaing; Brendish, Nathan J.; Poole, Stephen; Tanner, Alex R.; Borca, Florina; Smith, Trevor; Stammers, Matthew; Clark, Tristan W.
Highlights: Cohorting of patients at admission increases the risk of hospital-acquired COVID-19. Point-of-care testing (POCT) reduced time to results compared with laboratory PCR. POCT reduced the time that patients spent in cohort areas. POCT was associated with a reduction in the risk of hospital-acquired COVID-19. Summary: Objectives: Risk of hospital-acquired COVID-19 (HA-COVID-19) infection is increased by cohorting infected and non-infected patients together in assessment areas, whist awaiting laboratory PCR results. Molecular point-of-care tests (mPOCT) reduce time to results and improve patient flow but the impact on HA-COVID-19 is unknown. Methods: In this pre and post implementation study patients were evaluated across two time periods: March 1st to August 13th 2020, prior to the introduction of mPOCT in medical admissions areas, and 14th August 2020 to 1st April 2021, after mPOCT introduction. The primary outcome was proportion of HA-COVID-19 infection among all COVID-19 positive patients. Secondary outcome measures included time to SARS-CoV-2 results, length of time spent in the medical assessment area and comparison of local, regional and national proportions of HA-COVID-19. Results: 1988 patients were admitted through the acute medicine admission cohorting area and tested for SARS-CoV-2 prior to introducing mPOCT and 4640 afterwards. Median (IQR) time to SARS-CoV-2 result was 6.5 (2.1–17.9) hours prior to introducing mPOCT and 1.0 (0.8–1.3) hours afterwards ( p < 0.0001). Median (IQR) duration in the assessment cohort area was 12.0 (4.8–20.6) hours prior to introduction of POCT and 3.2 (2.0–5.6) hours afterwards ( p < 0.0001). The proportion of hospital-acquired COVID-19 cases was 108 (16.5%) of 654 prior to introducing mPOCT compared with 168 (9.4%) of 1782 afterwards, (HR 0.55, 95%CI 0.43–0.70; p < 0.0001). In the period following the introduction of mPOCT up to 1st April 2021 the median proportion of HA-COVID-19 was 13.6% (95%CI 8.2–18.9%) locally, compared with 43.8% (95%CI 37.8–49.9%) for all acute NHS trusts regionally and 30.9% (95%CI 28.4–33.5%) for all NHS trusts nationally. Conclusions: Routine mPOCT for SARS-CoV-2 was associated with reduced time to results, time spent in admission cohort areas, and hospital-acquired COVID-19, compared to laboratory PCR.